Dampak Ekonomi Wabah Penyakit Mulut dan Kuku Pada Peternak di Kabupaten Semarang - Khotimah, Yunita Khusnul; Wibowo, Hendri; Helbawanti, Octaviana; Suryani, Hasna Fajar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to determine the economic impact of the foot-and-mouth disease (FMD) outbreak on livestock farmers in Semarang Regency. The economic impact analysis reviewed includes prices, production, and income. The study was conducted in Tengaran District, Semarang Regency. There are 100 samples consisting of 77 farmer households affected by FMD and 23 farmer households not affected by FMD. This study was carried out from August to September 2023. The results showed that there was a price reduction of 13% from prices before the FMD outbreak. Milk production decreased by 43-68% from before being affected by FMD. The income of breeders affected by FMD is smaller than those who are not affected by FMD.